The wind blew - Hutchins, Pat, 1942-2017. (New York : Aladdin ; Toronto : Maxwell Macmillan Canada ; New York : Maxwell Macmillan International, 1993)
A rhymed tale describing the antics of a capricious wind.
"A hardcover edition of The wind blew is available from Macmillan Children's Books, Macmillan Publishing Company"--Verso t.p.
AD520L
Decoding demand: 54 (medium) Semantic demand: 67 (high) Syntactic demand: 84 (very high) Structure demand: 75 (high)
Accelerated Reader AR
edited hb 2015-06-16
Keywords: Winds; Winds; Stories in rhyme; Winds; Fiction; Fiction